Research of tax planning organization as one of the conditions for effective development of domestic enterprises - Грінько, Алла Павлівна; Бочуля, Тетяна Володимирівна; Волошенюк, Ірина Євгенієвна (Technology audit and production reserves, 2016)
Tax planning issues are investigated as one of the conditions for effective development of domestic enterprises, criteria by which make it possible to establish boundaries between tax planning and tax avoidance, interrelation of tax planning with accounting and balance policy of enterprise. Despite the fact that in theory the taxes do not have to manage all activities of enterprise, should not significantly change business philosophy, at practice taxes are powerful instrument of economic regulation that fully impact on level of strategic decision-making and leadership is forced to radically change tactics of enterprise activities. By using results of conducted analysis of impact of accounting and balance policy at tax obligations can be concluded that accounting policy as instrument of tax planning is powerful reserve for increasing efficiency of enterprise activity and balance policy is creative approach to the formation of financial reporting through the use of methods of accounting policy and creativity in accounting under applicable law and current regulatory documents. Methods of cost accounting, depreciation methods, variants of valuation of assets and indebtedness, possibility of creating reserve funds have an impact on reflection in financial statements results of activities of enterprise and respectively on size of tax base. Therefore their right choice will help management of the enterprise to choose necessary levers of tax planning.